The Effect Of Environmental Social Responsibility Program On Community Welfare By Strengthening Community Development At Ptpn Iv - Nafisah, Nur; Syahriza, Rahmi; Soemitro, Andi (UNIVERSITAS PAKUAN, 2017)
This study aims to see the effect of the Environmental Social Responsibility program on community welfare by strengthening community development. The data collection technique uses primary data, namely the distribution of questionnaires given to 59 respondents, the data analysis technique uses regression analysis moderating test, multicolonierity test, heteroscedasticity test, t test, and the coefficient of determination processed with SPSS 20 software. The results of this study indicate that the Environmental Social Responsibility program has a positive and significant effect on community welfare, and community development does not affect in improving the Social Responsibility program on community welfare.